LncRNA CAIF suppresses LPS‐induced inflammation and apoptosis of cardiomyocytes through regulating miR‐16 demethylation - Yan Wang (Wiley, 2021)
Abstract Background The long noncoding RNA, cardiac autophagy inhibitory factor (CAIF), and microRNA (miR)‐16 are reported to be involved in lipopolysaccharide (LPS)‐induced inflammatory responses and cell apoptosis in many diseases. Herein, we investigated the interaction between CAIF and miR‐16 in sepsis‐induced chronic heart failure (CHF). Methods The expression of CAIF and miR‐16 in plasma samples from sepsis‐induced CHF patients (n = 60) and healthy controls (n = 60) were measured using quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR). The correlations between CAIF and miR‐16 across plasma samples from patients with sepsis‐induced CHF and healthy controls were analyzed using linear regression. The messenger RNA (mRNA) levels of inducible nitric oxide synthase, C‐C motif chemokine 2 (CCL2), growth‐regulated alpha protein (CXCL1), and interleukin‐6 (IL‐6) were evaluated using qRT‐PCR while nuclear factor κB activation was evaluated using luciferase assay. Results The expression levels of CAIF and miR‐16 were downregulated in the plasma of sepsis‐induced CHF patients and were positively correlated in these patients. In cardiomyocytes, LPS treatment dose‐dependently decreased CAIF and miR‐16 levels. CAIF overexpression increased miR‐16 expression by demethylating miR‐16. CAIF and/or miR‐16 overexpression suppressed LPS‐induced CCL2, CXCL1, and IL‐6 expression at both the mRNA and protein levels. Analysis of cell apoptosis and western blot analysis showed that CAIF and/or miR‐16 overexpression inhibited LPS‐induced cardiomyocyte apoptosis by reducing Bax and cleaved caspase 3 levels and enhancing Bcl‐2 levels. Conclusion Our study is the first to report the abnormal expression of CAIF and miR‐16 in heart disease. CAIF plays a protective role in sepsis‐induced CHF by inhibiting cardiomyocyte apoptosis and inflammation, possibly by regulating miR‐16 demethylation.